Influence of Optical Defocus on Peripheral Vision - Rosén, Robert; Lundström, Linda; Unsbo, Peter (Investigative ophthalmology & visual science, 2011)
Peripheral optical corrections are often thought to give few visual benefits beyond improved detection acuity. However, patients with central visual field loss seem to benefit from peripheral correction, and animal studies suggest a role for peripheral vision in the development of myopia. This study was conducted to bridge this gap by systematically studying the sensitivity to optical defocus in a wide range of peripheral visual tasks. The spatial frequency threshold for detection and resolution in high and low contrast with stationary and drifting gratings were measured off-axis (20° nasal visual field) in five subjects with a peripheral optical correction that was varied systematically ±4 D. All visual tasks, except high-contrast resolution, were sensitive to optical defocus, particularly low-contrast resolution with an increase of up to 0.227 logMAR/D. The two myopic subjects exhibited a very low sensitivity to defocus by negative lenses for low-contrast tasks, whereas all subjects were equally affected by myopic defocus. Contrary to expectations, drifting gratings made little difference overall. Optical defocus as low as 1 D has a large impact on most peripheral visual tasks, with high-contrast resolution being the exception. Since the everyday visual scenery consists of objects at different contrast levels, it is understandable that persons with central visual field loss are helped by correction of peripheral refractive errors. The asymmetry in sensitivity to peripheral optical defocus in low-contrast tasks that was experienced by the myopic subjects in this study merits further investigation.